(untitled) (AYUSHDHARA, 2021)
Arma is a disease of Shukla mandala. In Ayurveda it has been described under Shuklagta Sadhya Vyadhi. This is a disease in which, a wing like triangular fibro-vascular layer or structure gradually encroaching towards the Krisna Mandala from either Kaneenika (Inner canthus) or Apanga Sandhi (outer canthus) of the eye. If this layer invades the cornea (Krisna Mandala) which is transparent in nature causes damage of the transparency of that part of cornea and thereby may cause disturbance in vision. On the basis of signs and symptoms described by the modern medical science, the disease ‘Arma’ can be correlated with Pterygium. This article gives a brief description about Nidanpanchak described in Samhita related to Arma in which Nidan, Purvroop, Roopa, and Sampapti ghatak described in detail. Along with Nidanpanchak detail description of types of Arma, Sadhya-asadhyatv, Chikitsa vivechan, Updrav, and Pathya-pathya mentioned in Samhita. The first and foremost method of treatment of Arma is Chedana Karma. However in the initial stage it can be treated with Lekhana Anjanas. Lekhan and Chedan is the main line of treatment of Arma. This article also defines the surgical procedure of Arma.